Hubungan rasionalitas penggunaan obat antihipertensi dengan luaran klinik di RS PKU Muhammadiyah Gamping - Sugiyono, Sugiyono; Putri, Shabela Alifia (University Of Darussalam Gontor, 2025)
Hypertension is an increase in a person's blood pressure above normal, namely systolic and diastolic blood pressure ≥140/90 mmHg. Rational use of medication can describe the health quality of hypertensive patients based on the parameters of the right indication, the right patient, the right drug and the right dose. The study aimed to determine the relationship between the rationality of using antihypertensive drugs and clinical outcomes in hypertensive patients who were hospitalized at PKU Muhammadiyah Gamping Hospital. The research method is non-experimental analytical with retrospective data collection using purposive sampling for data from January 2021-March 2024 with a sample size of 63 patients. The research results showed that the rationality of using antihypertensive drugs was based on an indication accuracy of 100%, patient accuracy of 100%, appropriate medication of 84.13% and dose suitability of 96.83%. Patients who received rational antihypertensive medication were 80.95% (51 patients) and 32 patients (50.79%) showed that blood pressure was achieved. Data analysis in research uses the Chi-Square test. The results of the Chi-square test obtained a p value = 0.096>0.05 so there is no relationship between the rationality of using antihypertensive drugs and clinical outcomes.